PENGABDIAN KEPADA MASYARAKAT : PENYULUHAN PELESTARIAN LINGKUNGAN DAN KEBERAGAMAN SOSIAL BUDAYA DI DESA GANTAR KABUPATEN INDRAMAYU - Nur Jihan, Adilla; Sabillah, Miftah; Al-Kautsar, Fajar; Syania Asri, Fauziah; Najmi Laila, Nurul; Sobirin (CV SWA Anugerah, 2025)
This Community Service Program (PKM) aims to raise awareness and understanding among members of the Al Mujahidin Mosque Taklim Council in Gantar Village, Indramayu, about the importance of environmental preservation and cultural diversity through counseling methods and active interaction. The main issues addressed are the low awareness of household waste management and the importance of preserving local cultural diversity. This program was conducted using counseling, question-and-answer sessions, and hands-on practice, focusing on the application of the 3R principles (Reduce, Reuse, Recycle) and strengthening the values of mutual cooperation (gotong royong) and communal work (kerja bakti). The results showed an increase in participants' understanding of household waste management, the utilization of inorganic waste into economically valuable products, and the importance of preserving local culture. Positive responses from participants were evident through their enthusiasm during the counseling and hands-on practice sessions. It is hoped that this program will have a sustainable impact on maintaining environmental sustainability and strengthening social and cultural relationships in the Gantar Village community. Keywords: Counseling, Environmental Preservation, Household Waste, Cultural Diversity, 3R.